Developing the socioculture-based thematic-integrative learning module for improving the learning motivation and the critical thinking - Sulistiya Ingwarni (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
This study aims to (1) produce thematic integrative learning modules based on sociocultural background feasible to increase student’s learning motivation and critical thinking, and (2) determine the effectiveness of the integrative thematic learning module. This research was included in the type of research and development (R D). Development procedures in this study adapting development procedures developed by Borg and Gall with steps, namely: (1) a preliminary study, (2) planning, (3) the design of the product, (3) field trials beginning, (5) the revision of the results of the initial field trials, (6) the main field trials, (7) the revision of the main results of field trials, (8) operational field trials, (9) the improvement of the final product. The subjects of the trial are fourth-grade students Jejeran, Bantul. The results show that (1) the integrative thematic learning module based on sociocultural background feasible according to media experts and subject matter experts with category ratings